Form measurement of a 0.1 mm diameter wire with a chromatic confocal sensor, with associated uncertainty evaluation. (7th June 2018) - Sanz, Claude; Giusca, Claudiu; Morantz, Paul; Marin, Antonio; Chérif, Ahmed; Schneider, Jürgen; Mainaud-Durand, Hélène; Shore, Paul; Steffens, Norbert
Abstract: The accurate characterisation of a copper–beryllium wire with a diameter of 0.1 mm is one of the steps to increase the precision of future accelerators' pre-alignment. Novelties in measuring the wire properties were found in order to overcome the difficulties brought by its small size. This paper focuses on an implementation of a chromatic-confocal sensor leading to a sub-micrometric uncertainty on the form measurements. Hence, this text reveals a high-accuracy metrology technique applicable to objects with small diameters: it details the methodology, describes a validation by comparison with a reference and specifies the uncertainty budget of this technique.